A regulamentação da terceirização e a proteção dos Direitos Fundamentais na relação de emprego - Oliveira, Otávio Romano de (2016)
This study aims to study the outsourcing, proposing an analysis in all its approaches in order to understand it in full. Initially shows the need for their appearance and their usage in enterprises, as well as the interests behind its spread. Then presents its applicability in other countries, in Brazil and legislative developments on the subject. The important thing is to stand out that outsourcing is a global phenomenon used in most countries of the world, while in Brazil it is often used in riotous fashion, why is synonymous with insecurity and is opposed by the supervisory bodies, prosecutors and Judges Job. The main point of the work is to defend the need for its regulation by Congress, since outsourcing is governed only by Precedent 331 of the Superior Labor Court, and is the object of immeasurable discussions in the Labour Judiciary. However, the rules that are being posed by the bill the House of Representatives No. 4,330 / 04 which will regulate the outsourcing and, after approval received the PLC number No. 30/2015 and is currently awaiting a vote by the Senate Federal, is the subject of much discussion and criticism of workers Unions and the judiciary organs, because they think, the way it is drafted, the new rules of outsourcing will bring a massive casualization and reduced fundamental rights for workers